IMPACT OF DIGITALIZATION ON TRANSFORMATIONS IN BUSINESS PROCESSES AND ACCOUNTING - Myronchuk , З.; Tsitska , Н.; Andrushko , Р.; Maletska , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article studies stages in the business processes of digitalization, formation of directions for accounting digitalization, identification of opportunities and threats, as well as current trends, advantages and disadvantages of digitization. It also defines peculiarities of implementing digital technologies as well as formation of directions and issues in accounting digitalization. The research on digitization of accounting in the context of business process digitalization is a relevant and contemporary problem. Modern trends, advantages and disadvantages of digitizing economic processes, as well as the main directions of accounting digitalization in business processes are substantiated in the work. The obtained results can be used by enterprise managers to create a digitalization process and determine further directions for accounting digitalization. Several aspects of transforming the accounting system are summarized, including the automation of routine processes, digitalization of accounting, use of artificial intelligence and cloud technologies. These technologies, when applied in business processes, reduce the probability of errors and ensure faster task completion. The article investigates the extent to which companies use digital technologies and innovative solutions in their accounting processes, the impact of digitalization on the efficiency and accuracy of accounting, and how digital solutions help avoid errors, reduce processing time, and facilitate faster access to financial information. By analyzing the data on application of digitalization technologies, the researchers substantiate the improved analytical capabilities of companies in the field of accounting, forecasting, and highlighting key financial indicators which influence their decision making. A questionnaire aimed to collect data for companies on the issues of digital technology use in accounting processes has been developed.